Metal-organic frameworks/polymer mixed matrix membranes for CO2 gas capture and separation in Li-air batteries - Puscalau, Constantin (2025)
Climate change and energy consumption share a direct relationship, a strong and increasingly alarming link caused by the use of fossil fuels. It is necessary to change consumption patterns and to introduce new technologies that can replace fossil fuel sources with renewable and very low carbon emission ones, which otherwise would continue to have a negative impact on our climate, as increasing quantities of harmful gases are expelled into the atmosphere. The need for energy storage capabilities has increased dramatically with the expanded use of renewable sources and electrochemical energy storage is a key technology in the world’s transition to more sustainable energy systems, with the potential to support a wide range of services needed for the transition.